Problems of investing in social housing and establishing municipal housing companies. - Shcherbyna, A.; Nikolaiev, V. (Ways to Improve Construction Efficiency, 2025)
From a scientific perspective, the approach proposed by international organizations to investing in social housing in the reconstruction of Ukrainian cities is considered. The basic model of a municipal housing company is analyzed, for its initial lending and further functioning on specific principles of self-sufficiency at the expense of rent for social housing. The current institutional approach to urban reconstruction through the creation of municipal rental social housing companies with the support of the European Commission and the EIB within the Ukraine Facility is analyzed, which is focused on new construction with combined financing (soft loans/donor funds) and further self-sufficiency through rental payments and cross-compensation between residential and non-residential premises. The aim of the article is to identify areas for improving the basic model, which is caused by the scale of needs in social housing, which cannot be satisfied only by the proposed mechanisms. The purpose of the study is to identify the limitations of the basic model, correlate them with the capabilities of current legislation and the extraordinary conditions of wartime, and propose directions for expanding the tools for forming a social housing fund. The methodology is based on a comparative analysis of the regulatory criteria for social housing, sources and forms of financing, types of ownership and management, local linkage and quality standards, involving 15 systemic criteria (target groups, purpose, type of housing, ownership/management, market position, etc.). The methodology of the analysis consists, on the one hand, in systematizing the essential characteristics of social housing, and on the other - in taking into account the specific needs of citizens in the war and post-war periods, as well as the specific conditions of specific cities. The conclusions and proposals concern a critical analysis and limitations of the application of the self-financing basic model for significantly reducing the cost of housing rent, as well as the problematic nature of its sustainable functioning if tenants are required to pay the full cost of housing and communal services. Therefore, the tasks of improving the model are justified..